Knowledge, Prevalence and Risk Factors of Violating Traffic Rules Among Adult Population - A Survey - SELVAM, SANTHANAM PANNEER; MOHANRAJ, KARTHIK GANESH (The journal of contemporary issues in business and government, 2020)
Road traffic injuries are one of the most important leading causes of death and disability in many of the developed and developing countries. Road accidents are major public health problems faced by the society. The crash can be defined as an incident or collision which may or may not lead to injury, occurring on a public road and involving at least one moving vehicle. In a developing country like India with a dense population there is a need to check the awareness level among the public about traffic signals and rules among the adult population, this survey was carried out. To check the awareness level among the adolescents population a questionnaire containing 10 questions was prepared. This survey was carried between the month of June 2019 to March 2020 among the adult population living in Chennai. This survey was conducted in an online platform where the participants responded to their answers. Finally the results were analysed and tabulated. Around 85% had knowledge and awareness of violating traffic signals and rules and suggested the need for having awareness camps to be organised by NGOs/Traffic Police/Government to create awareness among the public to obey traffic rules and 15% had no idea. The survey participants had moderate knowledge about road traffic regulations and most of them mentioned that prime speed, drivers lack of awareness about traffic regulation and laws, and drivers non-compliance with trafﬁc rules and regulation were the foremost important explanation for road traffic accidents